2000
DOI: 10.1007/s004150070070
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of gait in subcortical vascular encephalopathy by computerized analysis: a cross-sectional and longitudinal study

Abstract: In subcortical vascular encephalopathy (SVE) gait disturbance is a common and early clinical sign which might be used to monitor disease progression. In the absence of reliable scales and with regard to the equivocal results of highly complex gait imaging devices we assessed the natural course of SVE in a prospective study, using a new straight forward technique to quantify and compare sequential gait studies. We report the results of 300 computerized gait analyses in 119 patients with SVE and 63 age-matched c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
54
0
3

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 8 publications
5
54
0
3
Order By: Relevance
“…8,19,23,32,35 Two studies also reported a threshold effect of WMLs on mobility 7,31 with larger volumes of WMLs at baseline found to predict greater declines in mobility over time in longitudinal studies. 27,28,30,38 Finally, it has been reported that a significant increase in WML volumes occurs more frequently in mobility impaired people compared with people without such impairment. 37…”
Section: Relationship Between Wmls and Mobilitymentioning
confidence: 98%
See 2 more Smart Citations
“…8,19,23,32,35 Two studies also reported a threshold effect of WMLs on mobility 7,31 with larger volumes of WMLs at baseline found to predict greater declines in mobility over time in longitudinal studies. 27,28,30,38 Finally, it has been reported that a significant increase in WML volumes occurs more frequently in mobility impaired people compared with people without such impairment. 37…”
Section: Relationship Between Wmls and Mobilitymentioning
confidence: 98%
“…Even so, the associations between WMLs and impaired physical performance reported in several studies remained significant after controlling for vascular risk factors such as heart disease, hypertension, diabetes, homocysteine levels, and physical activity. 17,20,21,23,27 This suggests that vascular risk factors explain only a small component of the variance in the relationship between WMLs and physical performance.…”
Section: Mechanisms To Explain Relationships Between Wmls and Fall Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…The subjects wore force-sensitive insoles [14] that recorded with a sampling frequency of 100 Hz the normal force exerted by the floor while stepping during a period of 2 min of comfortable walking. Subjects walked along a 25 m long corridor, turned when they reached an end, and continued walking.…”
Section: Subjects and Extraction Of Time Seriesmentioning
confidence: 99%
“…3 Although we demonstrated that the different severity of WML and lacunar infarcts could partially account for this discrepancy, 1 even subjects with a similar degree of WML may have a different degree of gait impairment. 4 Because identical-appearing WML on conventional MRI are actually histopathologically heterogeneous, 5 it could be that only WML with the highest loss of microstructural integrity are related to gait disturbances. Moreover, MRI is not sensitive to early loss of microstructural integrity of the normal-appearing white matter (NAWM).…”
mentioning
confidence: 99%